Pancreatic transplantation. - Furtado, L; Bastos, C; Bastos, M; Mota, A; Roseiro, A; Fagulha, A; Paiva, I; Rodrigues, F; Gomes, L; Carvalheiro, M (Acta Médica Portuguesa, 1995)
The AA. report on their very limited experience with whole pancreatic transplantation. For the moment this is the only experience in Portugal, the detailed report of the 3 cases may be of some help to other Portuguese groups interested in starting this therapeutical approach for insulin-dependent end-stage renal failure patients. The main comments focus on the third simultaneous pancreas-kidney transplantation, which failed for technical reasons, mainly related to less than good selection of both donor and recipient. In all the three cases the technique preferred was the duodenocystostomy. The 2 first cases are doing very well, free of insulin and with normal glucose metabolism, at 15 and 7 months after grafting. The AA. also make some considerations on the indications, complications and follow-up of patients with pancreas-kidney transplantation.